P Value: Significance Is Not All Black and White. Issue 8 (August 2016) - Chakkera, Harini A.; Schold, Jesse D.; Kaplan, Bruce
Abstract : This brief review delves into the intricacies of the p-value and defines both the use and misuse of p-values in biomedical research. Alternatives such as confidence, credibility, prediction intervals, likelihood ratios, and false discovery rates, among others, are required to enhance the value of statistical testing, research interpretation, and results reporting.